Parametric Sensitivity Analysis of Organic Rankine Cycle for Waste Heat Recovery - Rouissi Roukaia; Cheggouri chourouk; Hadj ammar Ichrak (University of Shahid Hama Lakhdar - El Oued, 2025)
This study aims to evaluate and improve the performance of the Organic Rankine Cycle (ORC) as an effective means of recovering wasted heat in industrial applications that rely on low to medium temperature heat sources. The focus was on selecting the most suitable organic fluid and analyzing the impact of key operational variables on the cycle's yield. The Aspen Plus thermal simulation software was used to assess the performance of four different organic fluids: benzene, cyclohexane, toluene, and acetone. The sensitivity analysis results showed that increasing the evaporation pressure (30 bar) significantly improves net power output, with benzene achieving the highest value (2294 kW). Lowering the condenser pressure (1 bar) also enhances performance, with benzene recording the highest yield. The turbine efficiency (0.85) greatly contributes to increasing power production, with output rising from 1698 to 2443 kW for benzene. In contrast, pump efficiency had a relatively lower positive impact, with benzene's performance ranging from 2265 to 2299 kW. The analysis established that benzene is the best-performing fluid among the tested options, followed by cyclohexane, while acetone showed the weakest yield. This study contributes to improving thermal energy recovery efficiency and highlights the importance of precise operational adjustments and suitable fluid selection for high energy performance تهدف هذه الدراسة إلى تقييم وتحسين أداء دورة رانكين العضوية (ORC) كوسيلة فعالة لاستعادة الحرارة المهدرة في التطبيقات الصناعية التي تعتمد على مصادر حرارة منخفضة إلى متوسطة. كان التركيز على اختيار السائل العضوي الأكثر ملاءمة وتحليل تأثير المتغيرات التشغيلية الرئيسية على إنتاجية الدورة. تم استخدام برامج المحاكاة الحرارية Aspen Plus لتقييم أداء أربعة سوائل عضوية مختلفة: البنزين، السيكلوهكسين، التولوين، والأسيتون. أظهرت نتائج تحليل الحساسية أن زيادة ضغط التبخر (30 بار) يحسن بشكل كبير إنتاج الطاقة الصافية، حيث بلغ أعلى قيمة للبنزين (2294 كيلووات). كما أن خفض ضغط المكثف (1 بار) يعزز الأداء، حيث سجل البنزين أعلى إنتاجية. تسهم كفاءة التوربين (0.85) بشكل كبير في زيادة إنتاج الطاقة، حيث ارتفع الناتج من 1698 إلى 2443 كيلووات للبنزين. بالمقابل، كان لكفاءة المضخة تأثير إيجابي نسبي أقل. ...
Master's theses in chemical engineering
Keywords: ORC; WHR; Simulation; Sensitivity analysis; Aspen Plus; Working fluid; Efficiency; الكلمات المفتاحية : دورة ا رنكين العزهية، استخجاع الح ا خرة السيجورة، محاكاة، تحميل الحداسية، بخنامج مائع عسل، الكفاءة. ،Aspen Plus